(untitled) (American Journal of Islam and Society, 1985)
INTRODUCTION Political and economic developments in the post revolutionary Iran present a special dilemma to outside observers in general and to social scientists in particular as many developments do not seem to fit theusual political and economic categories with which the social scientists are normally familiar. As a result, most analysts of contemporary Iran, approaching the reality from the rigidly preconceived conceptual lenses, tend to grossly distort the actual picture. The contemporary situation in Iran is usually portrayed as one of utter chaos and turmoil with little or no hope for any progress in the future. It is seen as ruled by “emptyheadkid”, “conservative”, “brutal,” and “incompetent” mullahs who are bent upon destroying any signs of progress and civilization. Even the moderate analysts who seem to be less preoccupied with their biases and more cognizant of the new realities, appear to dismiss any long-term consequences of the current changes taking place in contemporary Iran. My major objective in the following pages is to develop an alternative image of the same reality. I argue here that slowly and gradually, a new political and economic order is emerging in Iran, whose broad objectives and outlines are clear. A major distinguishing characteristic of this order is its public welfarist orientation with special attention to the lower-middle and lower classes. And this order has the potential of so fundamentally transforming the political scene in Iran in the long run where the old issues and the old actors are most likely to be irrelevant to the new type of politics. Once successful, the political implications of this order will have a much wider effect on the Muslim world than commonly assumed. This paper has four sections. The first section deals with the ideology of the Islamic republic. Examining the ideas of the leading revolutionary thinkers, we shall try to establish a criteria against which the regime’s political and economic performance is to be assessed. The second section of the paper describes the nature of key political and economic institutions established in the aftermath of the revolution and their mode of functioning. The third part of the paper is concerned with the economic performance of the regime over the past five years. We shall assess its performance in two ways: (a) in light of the criteria established in the first part of the paper and (b) a brief comparison of the Islamic Republic’s five year performance with the prerevolutionary Iran’s last five-year plan (1973-1978). The final section of the paper summarizes the major conclusions of this study and also attempts to project a likely future scenario ...